2021
DOI: 10.1152/ajpheart.00206.2021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cerebrovascular dysfunction in the offspring from maternal electronic cigarette use during pregnancy

Abstract: Electronic cigarettes (E-cigs) have been promoted as harm-free or less-risky than smoking, even for women during pregnancy. These claims are made largely on E-cig aerosol having fewer number of toxic chemicals compared to cigarette smoke. Given that even low levels of smoking are found to produce adverse birth outcomes, we sought to test the hypothesis that vaping during pregnancy (with or without nicotine) would not be harm-free, and would result in vascular dysfunction that would be evident in offspring duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 103 publications
(64 reference statements)
1
10
1
Order By: Relevance
“…These data are consistent with extensive literature showing that chronic nicotine administration via transdermal application does not increase the risk of cardiovascular disease (JAMA Network, 1994;Joseph et al, 1996;Meine et al, 2005;Tzivoni et al, 1998). We have also reported previously that TEMPOL is able to rescue MCA function in adolescent and adult rat offspring that have MCA dysfunction secondary to maternal Ecig exposure during pregnancy (with or without nicotine; Burrage et al, 2021). Thus, it is not immediately clear why we saw TEMPOL rescue the blunted EDD response on D1-D3 for Ecigs but not for cigarettes in the present study.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…These data are consistent with extensive literature showing that chronic nicotine administration via transdermal application does not increase the risk of cardiovascular disease (JAMA Network, 1994;Joseph et al, 1996;Meine et al, 2005;Tzivoni et al, 1998). We have also reported previously that TEMPOL is able to rescue MCA function in adolescent and adult rat offspring that have MCA dysfunction secondary to maternal Ecig exposure during pregnancy (with or without nicotine; Burrage et al, 2021). Thus, it is not immediately clear why we saw TEMPOL rescue the blunted EDD response on D1-D3 for Ecigs but not for cigarettes in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…Nonetheless, a recent report (Jin et al, 2021) There is wide recognition that EVs can provide important endocrine signalling in health and disease (Stahl & Raposo, 2019). Previous work from our laboratory (Burrage et al, 2021) and others (Antoniewicz et al, 2016;Benedikter et al, 2018;Mobarrez et al, 2020) have found that Ecig exposure increases circulating EVs. Accordingly, we evaluated the temporal release of plasma EVs in our exposure groups.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations